THE INFLUENCE OF ECONOMIC GROWTH AND MINIMUM WAGES ON POVERTY IN SOUTHEAST SULAWESI PROVINCE - Saputri, Widya Eba; Aedy, Hasan; Asizah, Nur (JPEP (Jurnal Progres Ekonomi Pembangunan), 2022)
This study aims to examine and analyze the effect of economic growth and the minimum wage on poverty in Southeast Sulawesi Province. The sampling technique used purposive sampling. The type of data used in this study is secondary data from 12 regencies/cities of Southeast Sulawesi Province which is accessed through the website sultra.bps.go.id in the form of time series for the period 2010 to 2019. The analysis tool used is panel data regression with the help of software Eviews 10. The results show the coefficient of determination (R2) is 0.90, meaning that the independent variables of economic growth and the minimum wage affect 90% of the dependent variable of poverty. During the study period, economic growth had a significant positive effect on poverty. The minimum wage has a significant negative effect on poverty.